An exploration of how adult patients in a private mental health care facility experience singing in a group music therapy intervention in relation to their well-being - Mc Walter, Melissa (University of Pretoria, 2021)
Mini Dissertation (MMus (Music Therapy))--University of Pretoria, 2021.